Tratamento de água utilizando coagulantes orgânicos e filtros alternativos de fibra de coco e de carvão ativado a partir do bagaço da cana-de-açúcar - Ferreira, Rennan Soares (2025)
Water resources in Brazil have a variety of possible appliances, ranging from the preservation of terrestrial ecosystems to human consumption and electricity generation. In 2015, 97.3% of the water withdrawn was used for non-consumptive purposes, such as hydropower, while agriculture and livestock accounted for 56.5% of water usage for consumptive purposes. Preserving water resources is crucial to ensuring the quality of drinking water; however, the current situation is concerning. Inorganic coagulants, such as iron or aluminum salts, are commonly used in water treatment processes in Brazil but present environmental and health challenges. Therefore, organic coagulants, such as those derived from Moringa oleifera seeds and tannins, are promising alternatives. Recent studies also explore the use of unconventional materials, such as sugarcane bagasse and coconut fiber, as efficient filtering agents. This study aimed to evaluate the performance of organic coagulants and unconventional materials used in the construction of filters for water treatment. Coagulation/flocculation and sedimentation tests were conducted, and filtration was performed using filters made from coconut fiber and sands of 0 to 0.425 mm (G1) and 0.425 mm to 0.850 mm (G2), as well as activated carbon derived from sugarcane bagasse. Analyses of pH, electrical conductivity, turbidity, and apparent color were carried out to assess the efficiency of the coagulants and filters. The coagulant obtained from Moringa oleifera seeds was superior to tannin in the sedimentation stage when evaluating the parameters of turbidity and apparent color. Regarding the filters, the use of alternative materials, such as coconut fiber, showed satisfactory results, although inferior to the results obtained with the sand filter combined with activated carbon from sugarcane bagasse. The maximum turbidity and apparent color removal values achieved were 65% and 42%, respectively, for the coconut fiber filter, while the sand and activated carbon filter achieved removals of up to 99% and 94%, respectively. It was concluded that the sand and activated carbon filter from sugarcane bagasse was significantly better than the coconut filter for all parameters, except for electrical conductivity, and that the best combinations were obtained using both coagulants with the activated carbon filter.